Role of Regulatory T Cells in Chronic Obstructive Pulmonary Disease - Meghashree Sampath; Geetanjali Bade; Randeep Guleria; Anant Mohan; Sudip Sen; Anjana Talwar (Pulmonary Medicine)
Discussion: Characteristics changes were observed in patients with COPD. The compromised Tregs function, despite the increase in systemic inflammation, suggests a potential role of these cells in the pathogenesis of the disease.